2013
DOI: 10.1016/j.phymed.2013.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effect of leaf essential oil of Lippia gracilis Schauer (Verbenaceae)

Abstract: Medicinal plants are one of the most important sources of drugs used in the pharmaceutical industry. Among traditional medicinal plants, Lippia gracilis Schauer (Verbenaceae) had been used for several medicinal purposes in Brazilian northeastern. In this study, leaf essential oil (EO) of L. gracilis was prepared using hydrodistillation. Followed by GC-MS analysis, its composition was characterized by the presence of thymol (55.50%), as major constituent. The effects of EO on cell proliferation and apoptosis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(57 citation statements)
references
References 17 publications
(26 reference statements)
1
48
0
8
Order By: Relevance
“…B16-F10 melanoma cells exhibited the same sensitivity to thymol in two separate studies (39). This sensitivity was higher than a third study dealing with the same cell line (37), perhaps due to different incubation times and cell viability assays. Finally, its effect on P-815, K-562, CEM and MCF-7 cell lines was diverse, with EC 50 values ranging from 0.15-0.48 μΜ (33).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…B16-F10 melanoma cells exhibited the same sensitivity to thymol in two separate studies (39). This sensitivity was higher than a third study dealing with the same cell line (37), perhaps due to different incubation times and cell viability assays. Finally, its effect on P-815, K-562, CEM and MCF-7 cell lines was diverse, with EC 50 values ranging from 0.15-0.48 μΜ (33).…”
Section: Discussionmentioning
confidence: 71%
“…Of the cell lines we examined, thymol has only previously been tested again against HepG2 cells, where its EC 50 value was estimated to be >0.1 mΜ (37). It has been studied for its activity against several cancer lines, including HL-60 acute promyelotic leukemia cells, B16-F10 cells and finally P-815, K-562, CEM and MCF-7 cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…In animal model, Ferraz et al [99] confirmed that EO of Lippia gracilis possesses antitumor activity. Mice were subcutaneously transplanted with sarcoma 180 cells and treated by intraperitoneal route with EO for 7 days and they showed tumor growth inhibition rates of 38.5-41.9%.…”
Section: Salvia Officinalis Salvia Officinalis L (Common Sagementioning
confidence: 96%
“…Moreover, thymol was also able to induce caspase-independent apoptosis [22]. Research of Ferraz et al [99] showed cytotoxicity of Lippia gracilis EO treatment on HepG2 cells. Lippia gracilis is a medicinal plant, which has thymol as its major constituent.…”
Section: Salvia Officinalis Salvia Officinalis L (Common Sagementioning
confidence: 98%
“…Frankincense essential oil induced tumor regression in mice subcutaneously implanted with MIA PaCa-2 cells (Ni et al, 2014). Essential oil of Lippia gracilis considerably inhibited tumor growth in xenografted mice (Ferraz et al, 2013). Flavonoids isolated from Oxytropis falcata significantly inhibited tumor growth in mice transplanted with H22 cells (Yang et al, 2013).…”
Section: Xenografted Micementioning
confidence: 97%